Race science and surveillance: police as the new race scientists. (2nd January 2019) - Byfield, Natalie P.
ABSTRACT: This article examines the relationship between race and the urban in the United States through an examination of the role of surveillance – a growing global phenomena in contemporary western cities – and its uses in creating and maintaining boundaries of race, particularly because surveillance of racial and ethnic minority groups tend to be grounded in specific and bounded geographic locations. Using historical evidence and data from the New York Police Department (NYPD) Stop and Frisk program during the 2003–2013 period, this article asks whether or not, strategies of state surveillance of racial and ethnic minority groups should be interpreted as a 'new' type of scientific racism given the state's desire to deploy and its hyper-reliance on technologies to fulfil its surveillance role.